Housing Eviction, Displacement and the Missing Social Housing of Bucharest - Zamfirescu, Irina Maria (Calitatea Vieții, 2015)
After 1990, Romania privatized and restituted to the pre-communist owners its state owned housing. This led to a super-home ownership pattern and to a severe shrinking social housing sector. With thousands of people evicted and with no public investments in the social housing sector, Bucharest is among the cities with greatest number of people in Romania who need support for housing. This article offers an account of the linkages between eviction, housing restitution and the lack of involvement of the local public institution into social housing. I describe the political and administrative practices that prevent the emergence of efficient social housing programs. I move between scales, ranging from national, municipal and street dynamics, in order to describe and understand a recent case of eviction in Bucharest. With little to no support from the public authorities, more than 50 people have been living on the streets as a form of protest against Bucharest’s administration which promotes neo-liberalism and is complicit to furthering the poverty of the poor households.